The role of ELISA in the diagnosis of Alzheimer’s disease - Ye, Jiaer (Transactions on Materials, Biotechnology and Life Sciences, 2024)
As the world population ages, Alzheimer’s disease (AD) has emerged as a significant public health issue. The regulatory measures, clinical strategies, and even the scientific communications regarding AD all rely on the advancements in uncovering AD pathology, and the ability to recapitulate the disease-relevant players in a “gestalt” and clinically-applicable manner. Neurologists have sought to post mortem validation of AD pathologies (amyloid plaques and neurofibrillary tangles) in brain tissues; gradually, the weight is shifted to the detection of biological measures in the hope of diagnosing AD in its early phase before irreversible cognitive deterioration. Technologies that enable such early diagnosis or even prevention of AD, such as the enzyme-linked immunosorbent assay (ELISA), are emerging to obtain increasingly bigger roles in this field. Increasing the sensitivity and accuracy through enhancing the original ELISA with novel agents (nanoparticles as colorization agents etc) or improved protocols were the main approaches used. However, ELISA is also important as a lab staple, especially for the quantification of key AD biomolecules such as Ab42. ELISA connotates a more profound theme and future prospect of AD research: the entangling of biosensors development and the continued effort in deciphering of a more holistic map of AD.